2016
DOI: 10.5005/jp-journals-10016-1118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous 6 Months Oral Antioxidant Combination with Universally recommended Dosage in Idiopathic Male Infertility

Abstract: The aim of the present study was to observe the adverse effects of high level of reactive oxygen species (ROS) in idiopathic male infertility and the role of a combined antioxidant therapy for six months to overcome the detrimental effects of ROS. A prospective study including 185 infertile male was conducted at Institute of Reproductive Medicine (IRM) from January 2014 to April 2015. All the major sperm parameters as well as ROS, antioxidant level and the effect of high ROS level were evaluated before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Filipcikova et al in their study included 44 infertile men who were supplemented with lycopene for 3 months and found that seminal plasma's AA/DHA ratio improved in these cases [ 23 ]. Another study done by Chattopadhyay et al in 2016 showed an increase in motility and sperm count with a lowering of reactive oxygen species level, which gives a positive effect of Co Q10 on the participating patients [ 24 ]. Supplementation of omega-3 reduced DNA fragmentation, improved total antioxidant capacity (TAC) concentrations, and enhanced sperm motility as per studies done by Juan Carlos Martinex Soto et al and Gonzalez Ravina et al respectively [ 25 , 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…Filipcikova et al in their study included 44 infertile men who were supplemented with lycopene for 3 months and found that seminal plasma's AA/DHA ratio improved in these cases [ 23 ]. Another study done by Chattopadhyay et al in 2016 showed an increase in motility and sperm count with a lowering of reactive oxygen species level, which gives a positive effect of Co Q10 on the participating patients [ 24 ]. Supplementation of omega-3 reduced DNA fragmentation, improved total antioxidant capacity (TAC) concentrations, and enhanced sperm motility as per studies done by Juan Carlos Martinex Soto et al and Gonzalez Ravina et al respectively [ 25 , 26 ].…”
Section: Reviewmentioning
confidence: 99%